Sobre María Asenjo González, David Alonso García, y Silvia María Pérez González (eds.), Ciudades en expansión. Dinámicas urbanas entre los siglos XIV-XVI - Ramírez Méndez, Jessica (Historia Mexicana, 2024)
-